The Effect of Proprioceptive Training on Knee Joint Stability in Anterior Cruciate Ligament Injuries - Rizka Mutiara; Rabiatun Nasution; Siti Sarah Bintang (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2026)
Anterior Cruciate Ligament (ACL) injury is a disorder of the knee joint that often causes instability and decreased movement function. In addition to structural damage, this injury also impacts the decline in proprioception, which plays a role in neuromuscular control. This decline can disrupt balance and coordination of movement, thereby increasing the risk of recurrent injury and limitations in daily functional activities. Therefore, proprioceptive training is an important intervention in rehabilitation to improve knee joint stability. Objective: To determine the effect of proprioceptive training on knee joint stability in patients with ACL injury. The research method used a quasi-experimental design with a pre-test and post-test approach. The study sample consisted of ACL injury patients who were given proprioceptive training intervention for a certain period. Knee stability measurements were performed using functional and balance test instruments, namely the Single Leg Balance Test and the Star Excursion Balance Test (SEBT). Method: The study used a quasi-experimental design with a pre-test and post-test approach. The study sample consisted of ACL injury patients who were given proprioceptive training intervention for a certain period. Knee stability measurements were performed using functional and balance test instruments. Results: The study showed a significant increase in knee joint stability after proprioceptive training. This was demonstrated by an increase in static and dynamic balance scores and motor control compared to before the intervention. The discussion shows that proprioceptive training can improve sensorimotor integration, resulting in more optimal muscle response to changes in joint position. Conclusion: Proprioceptive training has a positive effect on improving knee joint stability in patients with ACL injuries. This intervention can be recommended as an important part of a physiotherapy rehabilitation program to improve knee function and reduce the risk of recurrent injury.